Peru's road to climate action: Are we on the right path? The role of life cycle methods to improve Peruvian national contributions - Vázquez-Rowe I. (2019)
This study is being published as part of the International Climate Initiative (IKI). The Federal Ministry for the Environment, Nature Conservation, Building and Nuclear Safety (BMUB) supports this initiative on the basis of a decision adopted by the German Bundestag. The authors would like to thank UN – Environment and the Peruvian Ministry of Environment (MINAM), namely Ignacio Sánchez and Adriana Zacarías, for technical support. Daniel Verán, Úrsula Cárdenas, Eduardo Parodi, Félix Cabrera, Alexis Dueñas, Marco Gusukuma, Alessandro Gilardino and Isabel Quispe, all from PUCP, are thanked for valuable scientific exchange. Ricardo Estrada, Manuel García Rosell and William Chata, from MINAM are thanked for their contribution with data to the current project. MSc student Gustavo Larrea-Gallegos thanks the Peruvian Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC) for financial support.